The Effect of PjBL with Copy The Master Method on the Skills of Writing Lesson Plans - Vivi Indriyani; Jasmienti Jasmienti; Ayu Gustia Ningsih (Yayasan Keluarga Guru Mandiri, 2023)
The skill of developing lesson plans is one of the competencies that teachers must have. The skills to develop these lesson plans can be learned while studying at universities. Based on observations, it was found that the skills of developing student lesson plans were still not in line with expectations, considering that students did not yet have an overview of the learning process in class. Based on this, learning methods are needed so that students are skilled in developing lesson plans. The purpose of this study is to determine the effect of using the Project-based Learning (PjBL) model with the Copy The Master method on the skills of developing lesson plans for prospective teacher students. This research type was quantitative research using experimental methods. The research design used was the Matching Pretest-Post-test Control Group Design. This research data collection technique used a test. The test given was a performance test, in which students made lesson plans based on the syllabus. Based on the results of the research and discussion, it can be concluded that using the PjBL Model with the Copy The Master method is effective in improving skills in developing lesson plans for prospective teacher students. Based on that, students can implement their knowledge when they become teachers.